Neuropsychological findings related to the presence of pre-surgical comorbid depression in Latin-American patients with mesial temporal lobe epilepsy and hippocampal sclerosis. (October 2020) - Figueiredo, Nathália Stela Visoná de; Cavalcanti, Maryane Mendes; Gaça, Larissa Botelho; Noffs, Maria Helena da Silva; Sousa, Arthur Victor Menezes; Alonso, Neide Barreira; Mazetto, Lenon; de Araújo Filho, Gerardo Maria; Yacubian, Elza Márcia Targas; Guilhoto, Laura Maria
Highlights: Patients with L- and R-HS had the expected neuropsychological profile for MTLE. No different neuropsychological outcome occurred in depression group. There was no difference when patients were analyzed regarding L- or R-MTLE-HS. Depression did not add any other cognitive impairment in this Latin-American series. Abstract: Purpose: To evaluate the neuropsychological findings related to the presence of pre-surgical comorbid depression in Latin-American patients with mesial temporal lobe epilepsy (MTLE) and unilateral hippocampal sclerosis (HS). Method: Patients with drug-resistant MTLE and unilateral, left (L-) or right (R-) HS were studied. To diagnose depression, psychiatrists with expertise in epilepsy applied a semi-structured interview based on DSM. The depression group (DG) included patients with a psychiatric diagnosis in addition to a Beck Depression Inventory (BDI) score >16 points, and the non-depression group (NDG) included those without this diagnosis and with a BDI score ≤16. We analysed two clusters of neuropsychological tests, which evaluated memory (Complex Rey Figure III, Logical Memory II and RAVLT VII) and attention plus executive functions (Stroop I/II/III and Trail Making A/B). Moreover, we calculated the z-scores (Zs) using a local control group. The DG was compared to the NDG, independently and according to the HS side, using non-parametrical analyses. Due to the multivariate analysis, the p-value was corrected by applying post hoc Bonferroni adjustment. Results: We analysed 65 patients. The NDG included 51 (78.4 %) patients, and the DG included 14 (21.5 %) patients. Pre-surgical comorbid depression occurred in eight patients with L- (n = 29) and in six patients with R-MTLE-HS (n = 36). All of these groups had similar gender, age, IQs, and years of schooling. Compared to the healthy subjects, the L-MTLE-HS patients had lower Zs in verbal episodic memory tests [Logical Memory II (p < 0.001), and RAVLT VII (p < 0.001)], and the R-MTLE-HS patients had lower scores in visual episodic memory [Complex Rey Figure III (p < 0.001)]. In the analysis of the DG vs. NDG, there were no differences in the clusters of tests of memory or in those of attention and executive functions. Moreover, when we analysed the patients according to HS side, no neuropsychological difference was observed in the DG and NDG in terms of L- and R-MTLE-HS. Conclusions: The patients with MTLE and unilateral HS in this study showed no differences in memory, attention and executive functions in relation to the presence of pre-surgical comorbid depression and independently of HS side. In this series from Latin-America, this psychiatric comorbidity did not affect cognition more than epilepsy alone.